Brief Historical Background of the Old World, Medieval and New Era Sports Facilities - Nurmatov Farkhat Abdualimovich (Research Parks Publishing LLC, 2021)
History has shown that sports competitions were held in ancient Greece. Each city had its own sports facilities for these competitions. Archaeological excavations have also proved this. For example, excavations in Mycenae, Crete, on the Aegean coast show images of games, exercises, and controversy. Exercises were used to train fighters for military training. Homer's Iliad and Odyssey describe mass running, wrestling, boxing, discus throwing, archery, and chariot racing (12th-9th centuries BC).